Determinants of Stock Prices : The Case of Zimbabwe - Oyama, T. (Washington, D.C. : International Monetary Fund, 1997)
This paper examines the general relationship between stock prices and macroeconomic variables in Zimbabwe, using the revised dividend discount model, error-correction model, and multi-factor return-generating model. Despite the large fluctuation in stock prices since 1991, this analysis indicates that the Zimbabwe Stock Exchange has been functioning quite consistently during this period. Whereas sharp increases in stock prices during 1993-94 were mainly due to the shift of risk premium that was caused by the partial capital account liberalization, the recent rapid increase in stock prices can be explained by the movements of monetary aggregates and market interest rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet